Answer:
see explanation
Explanation:
Calculate the distance between (x, y) and the 2 given points and equate them.
Using the distance formula
d =
with (x₁, y₁ ) = (x, y) and (x₂, y₂ ) = P(- 3, 4)
d =
Repeat with (x₁, y₁ ) = (x, y) and (x₂, y₂ ) = Q(2, - 1)
d =
Equating both distances
=
Square both sides
(2 - x)² + (- 1- y)² = (- 3 - x)² + (4 - y)² ← expand and simplify both sides
4 - 4x + x² + 1 + 2y + y² = 9 + 6x + x² + 16 - 8y + y²
subtract x² + y² from both sides
5 - 4x + 2y = 25 + 6x - 8y ( add 8y to both sides )
5 - 4x + 10y = 25 + 6x ( subtract 5 from both sides )
- 4x + 10y = 20 + 6x ( add 4x to both sides )
10y = 10x + 20 ( divide all terms by 10 )
y = x + 2 ← as required